2002
DOI: 10.1007/s00276-002-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Size of the collateral intercostal artery in adults: anatomical considerations in relation to thoracocentesis and thoracoscopy

Abstract: No detailed descriptions exist of the collateral intercostal artery which can provide an accurate anatomical basis for ensuring a low rate of vascular complications during thoracocentesis and thoracoscopy. Consequently the present study was undertaken to provide information on the origin, size and topographic relationships of the collateral intercostal artery. Ninety cadaveric adult intercostal spaces were dissected using standard procedures. The collateral intercostal arteries were exposed throughout their fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 3 publications
0
16
1
Order By: Relevance
“…This has been taken as a Safe Zone given the classical position of the intercostal neurovascular bundle in the subcostal groove, thus safely superior to the incision. Our data, together with a study published previously (Da Rocha et al, 2002), suggests that this is not the safest place. The correct Safe Zone should be between 50-70% of the way down an intercostal space to avoid the varyingly positioned superior intercostal neurovascular bundle and the inferior collateral artery.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…This has been taken as a Safe Zone given the classical position of the intercostal neurovascular bundle in the subcostal groove, thus safely superior to the incision. Our data, together with a study published previously (Da Rocha et al, 2002), suggests that this is not the safest place. The correct Safe Zone should be between 50-70% of the way down an intercostal space to avoid the varyingly positioned superior intercostal neurovascular bundle and the inferior collateral artery.…”
Section: Discussioncontrasting
confidence: 45%
“…We are not attempting to comment on the frequency of occurrence of the veins, arteries and nerves in the principal neurovascular bundles. The nature of the collateral arteries has been reported elsewhere (Da Rocha et al, 2002). To achieve the aim of our study, the important goal was accurate recording of position, even at the expense of identifying every structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of thoracic aortograms [25] showed that the degree of tortuosity of the ICA increased with age, especially in those >60 years old where its appearance could be almost sinusoidal. Finally, an additional vessel located in the inferior region of the ICS, the collateral artery, has been reported in cadaveric dissection studies [24,26]. In all cases, a collateral artery arose from the ICA between the corresponding vertebra and angle of the rib, and could be as large as the ICA.…”
Section: Discussionmentioning
confidence: 99%
“…The major cause of haemothorax in thoracentesis is laceration of the posterior intercostal artery or its collateral branches [9,12]. Reports of intercostal artery laceration and subsequent haemothorax have existed in the literature since 1970 [2], but at present there is no comprehensive description of the posterior intercostal and collateral vascular anatomy [3]. Another procedure gaining popularity among clinicians for resection of lung tumours is video-assisted thoracic surgery (VATS).…”
Section: Introductionmentioning
confidence: 99%